IMPLEMENTASI PERLINDUNGAN DAN PEMENUHAN HAK PEREMPUAN KORBAN KEKERASAN SEKSUAL DI MAKASSAR - Mutmainnah, Mutmainnah; Aisyah, St.; Hisbullah, Hisbullah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
Sexual violence against women continues to increase. Komnas Perempuan recorded that there were 226,062 cases of sexual violence against women in 2020 increasing to 338,496 cases in 2021. Through Law Number 31 of 2014 concerning Protection of Witnesses and Victims, it contains rights that women should receive as victims of sexual violence. This study aims to reveal the implementation of the rights of women victims of sexual violence in the city of Makassar. This type of research is a qualitative field research with normative juridical and normative theological approaches. The results of the study show that sexual violence in Makassar City is still relatively high. In addition, the protection of the rights of women victims of sexual violence has not been implemented properly due to the lack of capacity of law enforcement to understand victims' rights, impunity for perpetrators, limited escort staff, culture of siri' society, and limited access to legal aid in the regions are obstacles in protecting and fulfilling the rights of victims of sexual violence.